Increasing Interest in Inclusive Education in the Context of Action Plan for the Development and Enhancement of Special Education during the Fourteenth Five-Year Period in China: An Analysis of Baidu Index Data - Hongmei Long; Meijie Wang; Qinyi Tan; Pan Chen; Luyan Teng (Journal of Education, Health and Sport, 2022)
Objective: Current evidence shows that public interest in inclusive education has been rising since the implementation of Action Plan for the development and enhancement of special education during the Fourteenth Five-Year period in China. The aim of this study was to quantify recent trends in public interest and related online search behavior for inclusive education in the context of this Action Plan.